The Mediating Effects of Brand Preference to Customer Satisfaction - Jasin Mochammad, Dytta Novrianda, Pudji Astuti, Christina Catur Widayati, Agus Zainul Arifin (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
The purpose of this study is to analyze the influence of brand preference to customer satisfaction (advertiser). Samples consists of one hundred and twenty persons of decision makers of government advertisemen programs in various government agencies and state owned companies. Data was collected by using self-completed questionnaire. Structural Equation Modelling used to analyze the indicator variables, latent variables and measurement error variables to determine of causal brand awareness, brand association, brand extension, perceived quality to customer satisfaction through brand preference of Sindo Media (MNC Group). The finding reveals a significant influence on mediated variables. While Brand awareness, Brand association, Brand extension, Perceived quality, has a significant influence on customer satisfaction. That means Brand preference has significant influence to customer satisfaction.